2018
DOI: 10.2991/ijcis.11.1.51
|View full text |Cite
|
Sign up to set email alerts
|

A computer aided analysis scheme for detecting epileptic seizure from EEG data

Abstract: This paper presents a computer aided analysis system for detecting epileptic seizure from electroencephalogram (EEG) signal data. As EEG recordings contain a vast amount of data, which is heterogeneous with respect to a time-period, we intend to introduce a clustering technique to discover different groups of data according to similarities or dissimilarities among the patterns. In the proposed methodology, we use K-means clustering for partitioning each category EEG data set (e.g. healthy; epileptic seizure) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Association rules are used to find the relationship between etiology, syndrome, symptoms and herbal prescription of infectious diseases. In another work, Kabir et al [169] presented the system to detect epileptic seizure from EEG signal using SVM, Naive bayes and logistic regression. Results showed that k-mean clustering can handle EEG data efficiently in order to detect epileptic seizure.…”
Section: Clusteringmentioning
confidence: 99%
“…Association rules are used to find the relationship between etiology, syndrome, symptoms and herbal prescription of infectious diseases. In another work, Kabir et al [169] presented the system to detect epileptic seizure from EEG signal using SVM, Naive bayes and logistic regression. Results showed that k-mean clustering can handle EEG data efficiently in order to detect epileptic seizure.…”
Section: Clusteringmentioning
confidence: 99%
“…Epileptic seizures not only harm the sensory, motor, and functional aspects of the body, but they also affect the consciousness, memory, and cognition of patients [ 5 ]. Therefore, it is of great practical significance to develop an effective detection approach for epileptic seizures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, electrical signals recorded using an EEG are believed to provide more information about brain activity and can be collected in a non-invasive manner [7][8][9]. The placement of electrodes for recording the EEG signal is guided either by the benchmark set by the American Academy of Sleep Medicine (AASM) [10,11]; or by the international 10-20 system for the placement of electrodes [10,12].…”
Section: Introductionmentioning
confidence: 99%